Loss of glycerol catabolism confers carbon-source-dependent artemisinin resistance in Mycobacterium tuberculosis - Martini, María Carla (2024)
In view of the urgent need for new antibiotics to treat human infections caused by multidrug-resistant pathogens, drug repurposing is gaining strength due to the relatively low research costs and shorter clinical trials. Such is the case of artemisinin, an antimalarial drug that has recently been shown to display activity against Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis. To gain insight into how Mtb is affected by artemisinin, we used RNAseq to assess the impact of artemisinin on gene expression profiles, revealing the induction of several efflux pumps and the KstR2 regulon. To anticipate the artemisinin resistance-conferring mutations that could arise in clinical Mtb strains, we performed an in vitro evolution experiment in the presence of lethal concentrations of artemisinin. We obtained artemisinin-resistant isolates displaying different growth kinetics and drug phenotypes, suggesting that resistance evolved through different pathways. Whole-genome sequencing of nine isolates revealed alterations in the glpK and glpQ1 genes, both involved in glycerol metabolism, in seven and one strains, respectively. We then constructed a glpK mutant and found that loss of glpK increases artemisinin resistance only when glycerol is present as a major carbon source. Our results suggest that mutations in glycerol catabolism genes could be selected during the evolution of resistance to artemisinin when glycerol is available as a carbon source. These results add to recent findings of mutations and phase variants that reduce drug efficacy in carbon-source-dependent ways.